Mary Wollstonecraft on Politics and Friendship - Frazer, E (Wiley Blackwell, 2008)
How, exactly, might friendship be relevant to politics? Friendship between political actors can be hypothesised to have specific effects; friendship between individuals in society can be hypothesised to have specific political outcomes; or friendship and politics can be understood to be conceptually connected. Mary Wollstonecraft makes friendship a central concept in her political theory of social justice and good government. This article analyses how politics and friendship are related in her texts, exploring her arguments that friendship in society is a condition of just government, but also suggesting that for Wollstonecraft friendship and citizenship are congruent with one another, and hence that the connection between politics and friendship is conceptual as well as causal.